Perancangan Visual Asset Game Pixel Art Jejak Pagaruyuang sebagai Media Interaktif Pengenalan Budaya Minangkabau - Altalarik Hamzah; Sheanny Ocmi Sakti (Lembaga Yasin AlSys, 2026)
Although the use of games as a medium for introducing culture continues to develop, studies that specifically discuss the process of translating Minangkabau cultural identity into pixel art visual assets remain limited. This study aimed to design the visual assets for the game “Jejak Pagaruyuang” as an interactive medium for introducing Minangkabau culture. The study employed a research and development approach using the Multimedia Development Life Cycle model, which includes the stages of concept, design, material collection, production, and testing. Data were obtained through direct observation at Istana Basa Pagaruyung, visual documentation, literature review, and functional testing, and were then analyzed descriptively and qualitatively based on visual appropriateness, asset consistency, and functional success. The results of the study produced main character, NPC, environment, cultural object, user interface, and supporting animation assets developed using Aseprite. Alpha testing of five components showed that all assets functioned in accordance with the design. These findings indicate that form simplification, color palette consistency, silhouette readability, and the appropriateness of cultural attributes are important elements in the design of culture-themed pixel art. This study contributes to the development of visual communication and digital cultural games and broadens understanding of visual asset design based on local cultural identity.